Understanding crime: a multilevel approach - Ward, Tony (Psychology, crime & law, 2019)
According to contemporary scientific research human behaviour arises from a dynamic interplay between biological, psychological, cultural, and social processes. Therefore, because of their tendency to focus on only one of these levels of explanations, traditional criminology and forensic psychology can only offer partial understandings of crime. We contend that the best way forward for researchers and practitioners is to bring together different disciplinary perspectives and to develop integrative pluralistic explanations of crime.